Penguatan Pendidikan Seksual Sejak Dini melalui Media PowerPoint Interaktif pada Siswa SD Negeri Gebang Surakarta (Lembaga Pengembangan Kinerja Dosen, 2026)
The PPA Symphony recorded 7,842 cases of violence against children by mid-2024, indicating the need for preventive efforts through early sexual education. Sexual education for children aims to improve their understanding of body awareness, body privacy, and self-protection from inappropriate behaviors. This community service activity aimed to increase students’ understanding of sexual education through interactive PowerPoint media. The activity was conducted at SD Negeri Gebang Surakarta on April 25, 2025, involving 63 students from grades 3, 4, and 5. The method used was an interactive lecture supported by PowerPoint media, storytelling, and mini games. Evaluation was conducted using pre-test and post-test questionnaires to measure students’ knowledge. The results showed an increase in the average knowledge score from 9.827 in the pre-test to 10.210 in the post-test. These findings indicate that interactive PowerPoint media is effective in improving students’ understanding of basic sexual education, particularly regarding body parts, body privacy, safe and unsafe zones, and strategies for refusing uncomfortable behaviors. Therefore, interactive learning media can serve as an effective educational strategy to strengthen early sexual education among elementary school students.